Mechanisms of Teaching the German Language Through Traditional and Innovative Methods (Eurasian Journal of Research, Development and Innovation, 2022)
Method is a Latin word that means to search for a new way of teaching, to find an easy way of explanation, to search. In pedagogical training manuals, the methods of equipping students with knowledge, skills and abilities and their mastery are called teaching methods